Implementasi Hukum Administrasi Negara Dalam Perspektif Maslahah Mursalah - M, Madhur; Mas'odi, Mas'odi (Syura: Journal of Law, 2023)
State administrative law has an important role to create a good and orderly system of government. It is hoped that state administrative law wiil function to expedite the task of administering the state and provide legal guarantees to citizens and protect all people. This is also in line with the objektives of maslahah mursalah, so that the implementation of state administrative law can be integrated with exploring the values of maslahah mursalah. The purpose of this study is to find out how the role of islamic law (maslahah mursalah) in the implementation of state administrative law. The benefit of this research is to find out how far maslahah mursalah is applied to state administrative law. This study uses the usul fiqh approach as an epistemological basis in the application of state administrative law. This research is a qualitative reseach with descriptive analysis and library reseach. The results of this study are to find a common goal between state administrative law and maslahah mursalah, and the effectiveness of implementing state administrative law besed on maslahah mursalah values.